Relationship between Brain-Derived Neurotrophic Factor and Schneiderian First Rank Symptoms in Antipsychotic-Naïve Schizophrenia - Kalmady, Sunil; Venkatasubramanian, Ganesan; Shivakumar, Venkataram; Jose, Dania; Ravi, Vasanthapuram; Gangadhar, Bangalore N. (Frontiers in Psychiatry, 2013)
Neurodevelopmental aberrations influenced by neurotrophic factors are among the important paradigms to understand schizophrenia pathogenesis. Among various neurotrophic factors, Brain-Derived Neurotrophic Factor (BDNF) is strongly implicated by previous research studies. Evaluating co-morbidity free, antipsychotic-naïve schizophrenia patients for BDNF levels and examining the correlates of this factor with symptoms might facilitate elucidation of its pathogenetic role without confounds of potential influencing factors. In this study, 59 co-morbidity free, antipsychotic-naïve schizophrenia patients were compared with 60 healthy controls for serum BDNF levels. In addition, the relationship between Schneiderian First Rank Symptoms (FRS) and BDNF level in patients was examined. As a group, schizophrenia patients (28.8±11.7 ng/mL) had significantly lower serum BDNF than healthy controls (34.9±8.2 ng/mL) after controlling for the potential confounding effects of age and sex (F=7.8; p=0.006). Further analyses revealed FRS status to have significant effect on plasma BDNF after controlling for the potential confounding effects of age and sex (F=4.5; p=0.01). Follow-up posthoc analyses revealed FRS(+) patients to have significant deficit in plasma BDNF level in comparison with healthy controls (p=0.002); however, FRS(─) patients did not differ from healthy controls (p=0.38). Our study observations add further support to the role for BDNF in schizophrenia pathogenesis and suggest a potential novel link between deficient BDNF and FRS.